(untitled) (Nepalese Journal of Ophthalmology, 2020)
Introduction: Corneal blindness, though treatable, contributes largely to the burden of blindness. With 1.2 million existing cases of corneal blindness in India, the demand for cornea collection is increasing. 69349 corneas were collected in 2018-19 but it is much less than what is needed. Faulty perceptions and unwillingness are two major hurdles against a scenario favourable towards eye donation. The objectives of the study was to assess the perception and willingness towards eye donation and the socio-demographic variables that affect such perception and willingness, in an urban community of West Bengal. Materials and methods: In this cross-sectional study conducted among adult residents of the urban field practice area of Medical College Kolkata, data was collected from randomly selected eligible members, one each from all the available families by interviewing them using a validated pre tested schedule. Results: Eighty nine (52.3%) among 170 interviewed participants had Secondary level education or higher, 49.4% had outdoor engagement. 128 participants reported ocular morbidity in the family but only 126 had heard about eye donation. 98 (77.8%) of these 126, had favourable perception towards eye donation. Among these 98 participants, 40 were willing to pledge for eye donation. Higher education and outdoor engagement significantly predicted favourable perception, while willingness significantly increased with participants belonging to higher socio-economic class and with higher education. Conclusions: Compared to favourable perception, willingness of pledging eyes was lesser due to various false notions. Proper education through usage of means of mass communication and stress upon school education is needed to address these hurdles.